Integrating reproductive health services into HIV care: strategies for successful implementation in a low-resource HIV clinic in Lilongwe, Malawi. Issue 1 (22nd April 2015) - Phiri, Sam; Feldacker, Caryl; Chaweza, Thomas; Mlundira, Linly; Tweya, Hannock; Speight, Colin; Samala, Bernadette; Kachale, Fannie; Umpierrez, Denise; Haddad, Lisa
Abstract : Background: Lighthouse Trust operates two public HIV testing, treatment and care clinics in Lilongwe, Malawi, caring for over 26 000 people living with HIV, 23 000 of whom are on antiretroviral treatment (ART). In August 2010, Lighthouse Trust piloted a step-wise integration of sexual and reproductive health (SRH) services into routine HIV care at its Lighthouse clinic site. The objectives were to increase uptake of family planning (FP), promote long-term reversible contraceptive methods, and increase access, screening and treatment for cervical cancer using visual inspection with acetic acid. Methods and results: Patients found integrated SRH/ART services acceptable; service availability appeared to increase uptake. Between August 2010 and May 2014, over 6000 women at Lighthouse received FP education messages. Of 859 women who initiated FP, 55% chose depot medroxyprogesterone acetate, 19% chose an intrauterine contraceptive device, 14% chose oral contraceptive pills, and 12% chose an implant. By May 2014, 21% of eligible female patients received cervical cancer screening: 11% (166 women) had abnormal cervical findings during screening for cervical cancer and underwent further treatment. Conclusions: Several lessons were learned in overcoming initial concerns about integration. First, our integrated services required minimal additional resources over those needed for provision of HIV care alone. Second, patient flow improved during implementation, reducing a barrier for clients seeking multiple services. Lastly, analysis of routine data showed that the proportion of women using some form of modern contraception was 45% higher at Lighthouse than at Lighthouse's sister clinic where services were not integrated (42% vs 29%), providing further evidence for promotion of SRH/ART integration.